Integrating Reading and Writing Skills through Blackout Poetry - Fera Sulastri; Melisa Sri (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
This study aimed at investigating students’ perception of their improvement after the project of blackout poetry writing. 51 Students in the creative writing class took a part in the project for three months. Open-ended questionnaires were used to investigate their improvement both in reading and writing. Based on the data analyzed thematically, it is found that most of the students got the improvement in both skills. (1) By reading text continuously, they get the appropriate right words for writing blackout poetry, (2) for reading specifically, the student’s scanning technique becomes easier to practice, and (3) better reading comprehension leads them to make better poetry. Keywords: Writing, Reading, Blackout Poetry, Creative Writing